The effect of eccentricity at beam support to beam stiffness - Mohd Ali, Ahmad Zurisman (2005)
A beam reacts to loading through bending action. Therefore, beam bending stiffuess can be represented by deflection. Theoretically, beam stiffuess is governed by span length, elastic modulus, moment of inertia and support type. In the analytical analysis, beams are assumed simply supported or fixed supported However, based on real cases and lab experiments there are other factors that are not included theoretical equation but effect to the beam stiffuess Factors such as eccentricity between beam neutral axis and beam support (vertical eccentricity), pour stop stiffuess in composite beam/slab effect and column size effect were analyzed in this study. The effects were studied using plane stress element finite. Pour stop stiffuess were modelled using spring element. From the analysis, vertical eccentricity does not give significant effect to beam stiffuess and it can be neglected. The pour stop provides stiffuess of 25000kN/m at the outer support. Beam deflection is independent with column deflection when column width is three times bigger than beam depth.